Phenylalanine ammonia lyase: new insights from Piperaceae species - Morandim-Giannetti, Andreia de Araújo; Felippe, Lidiane Gaspareto; dos Santos, Vânia Aparecida de Freitas Formenton Macedo; Kato, Massuo Jorge; Furlan, Maysa (Eclética Química, 2022)
The enzyme PAL (phenylalanine ammonia lyase) mediates the key entry point to the general phenylpropanoid pathway, which is involved in the lignification process and in the formation of a myriad of secondary compounds in plants that show a variety of biological activities. Soluble fractions containing PAL extracted from Piper and Peperomia species had the optimal catalytic activity analyzed by statistical design model. This analysis revealed that the best conversion of L-phenylalanine to trans-cinnamic acid was pH 9.3 and 58 °C after 25 h, corroborating interesting thermal stability. Additionally, the pre-purification of PAL using ammonium sulfate precipitation (25-55%) increased its specific activity, approximately 133% in P. aduncum and more than 900% in P. crassinervium. The content of lignin was higher for P. tuberculatum (25.71%), while only a small amount of lignin was observed in Peperomia blanda (11.95%). It is interesting to note that Peperomia plants are succulent and without significant amounts of lignin. However, the phenylpropanoid biosynthetic pathway is apparently addressed to produce predominantly tetrahydrofuran lignans with biological interest.